Why Uk non-financial firms hedge fx risk - Adenuga, Prince (2021)
Abstract This paper aims to investigate the determinants of hedging by UK non-financial firms. It uses disclosures from annual reports of 221 UK firms and data from the database ‘data stream’. The data collected from the annual reports span over four years (2016-2019) and the key word approach is used to find relevant information pertaining to the hedging activities of firms. The logit regressions show that larger firms and those that are exposed to FX risk are more likely to hedge FX risk. This thesis goes on further to demonstrate the bias that exists when FX debt hedgers are included in the non-hedger sample. It is found that its inclusion can prevent the discovery of links between important firm specific factors and the decision to hedge.